CSR, PROFITABILITAS DAN UKURAN PERUSAHAAN SERTA PENGARUHNYA TERHADAP RETURN SAHAM PADA PERUSAHAAN PROFIT YANG TERDAFTAR DI INDEKS SRI KEHATI PERIODE TAHUN 2017-2019 - Andini Nurwulandari (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2019)
Today's corporate companies face growing pressure to perform their operations professionally from a variety of stakeholders, including society, workers, and shareholders. Profitability is a hot subject in society, which places more pressure on businesses to share details. This study is qualitative in nature and takes a descriptive-analytic approach. This study established that a company's CSR metric has a detrimental effect on its stock returns. Profitability has a favorable impact on the stock return of a firm. Meanwhile, the business size indicator has a favorable impact on the returns on company shares.